Impacts of the pandemic on agribusiness in the municipality of Guaraí – TO (Research, Society and Development, 2022)
The pandemic caused by the coronavirus has been considered an unprecedented event in history, as people have suffered serious impacts in various areas of life, especially the world economy. In this sense, it can be said that covid-19 has had repercussions in different ways on the production, distribution and supply of foos and agricultural inputs across the country. Based on this premise, the present research aims, in general, to address the Impact of the Pandemic on Agribusiness in the municipality of Guaraí-TO, making a practical and local comparison with what is known in scientific records on the subject, in a specific way. Seeks to report on the general context and economic effects on agribusiness, address the impacts of the pandemic on the agricultural sector and point out the impacts of the pandemic on the agricultural sector. The methodology used was a mix between the bibliographic review and analysis of field research results, the latter being carried out with six companies in the agricultural sector that participated in the research by answering a question form to measure the behavior of local commerce in the face of the pandemic. And the measures imposed to contain the disease.